The effect of statin administration on IL-6 and IL-1b expression in peripheral blood mononuclear cells of a hypertensive patient with SARS-CoV-2 spike protein stimulation - Andrianto Andrianto; Budi Susetyo Pikir; Rizki Amalia; Teuku Yusrizal; Fatimah Alzahra; Maya Qurota A’yun; Michael Jonatan (Medicinski Glasnik, 2022)
Aim The infection of the SARS-CoV-2 virus potentially causes a cytokine storm with elevated IL-6 and IL-1β levels. Statin therapy was common among COVID-19 patients due to their cardiovascular comorbidities. However, the effect of statins on COVID-19 infection is unclear. The aim of this study was to evaluate the impact of statin administration on IL-6 and IL-1β level in peripheral blood mononuclear cells (PBMCs) after SARS-CoV-2 spike protein stimulation. Methods The PBMCs were isolated from a hypertensive patient and stimulated by the SARS-CoV-2 subunit S1 spike protein. The PBMCs were then divided into four treatment groups and treated with simvastatin at various doses (10 µM, 25 µM, 50 µM, and control). IL-6 and IL-1β were measured from the supernatant using the ELISA method. Results The stimulation of SARS-CoV-2 spike protein in PBMC cell culture statistically increased IL-6 and IL1β expression of 5.2 and 35.07 fold, respectively (p<0.05). The expressions of IL-6 and IL-1β were not statistically significant among three simvastatin doses and control. Conclusion Statin administration did not have significant effect on IL-6 and IL-1β levels in PBMCs after SARS-CoV-2 spike protein stimulation in this study, a further study is needed.